On the Systematic Occurrence of Compound Cold Spells in North America and Wet or Windy Extremes in Europe - Gabriele Messori; Davide Faranda (Geophysical Research Letters)
Abstract The repeated co‐occurrence of cold spells over Eastern North America and wet or windy extremes over Western Continental Europe during recent winters, has led to hypothesize a link between the two. Here, we analyze the interplay between the large‐scale atmospheric circulation and co‐occurring cold spells in North America and wet or windy extremes in Europe. We collectively term these occurrences compound cold–wet–windy extremes. We leverage a recent approach grounded in dynamical systems theory, which provides an analytically and computationally efficient analysis of spatially resolved, multivariate climate extremes. We find that there are specific, recurrent large‐scale atmospheric circulation patterns systematically associated with both the individual extremes and co‐occurring cold–wet–windy anomalies. Evidence for this is also found when focusing on compound cold–wet–windy extremes, although with a weaker signal. This motivates further analyses focusing specifically on the statistics and drivers of these compound extreme occurrences.